A Comprehensive Safety Trial of Chimeric Antibody 14.18 With GM-CSF, IL-2, and Isotretinoin in High-Risk Neuroblastoma Patients Following Myeloablative Therapy: Children’s Oncology Group Study ANBL0931 - Ozkaynak, M. Fevzi; Gilman, Andrew L.; London, Wendy B.; Naranjo, Arlene; Diccianni, Mitchell B.; Tenney, Sheena C.; Smith, Malcolm; Messer, Karen S.; Seeger, Robert; Reynolds, C. Patrick; Smith, L. Mary; Shulkin, Barry L.; et al. (Frontiers in Immunology, 2018)
Purpose: A Phase 3 randomized study (COG ANBL0032) demonstrated significantly improved outcome by adding immunotherapy with ch14.18 antibody to isotretinoin as post-consolidation therapy for high-risk neuroblastoma (NB). This study, ANBL0931, was designed to collect FDA-required safety/toxicity data to support FDA registration of ch14.18. Experimental Design: Newly diagnosed high-risk NB patients who achieved at least a partial response to induction therapy and received myeloablative consolidation with stem cell rescue were enrolled to receive 6 courses of isotretinoin with five concomitant cycles of ch14.18 combined with GM-CSF or IL2. Ch14.18 infusion time was 10-20 hours per dose. Blood was collected for cytokine analysis and its association with toxicities and outcome. Results: Of 105 patients enrolled, five patients developed protocol-defined unacceptable toxicities. The most common Grade ≥3 non-hematologic toxicities of immunotherapy for cycles 1-5, respectively, were neuropathic pain (41%, 28%, 22%, 31%, 24%), hypotension (10%, 17%, 4%, 14%, 8%), allergic reactions (3%, 10%, 5%, 7%, 2%), capillary leak syndrome (1%, 4%, 0%, 2%, 0%), and fever (21%, 59%, 6%, 32%, 5%). The 3-year event-free survival and overall survival were 67.6±4.8% and 79.1±4.2%, respectively. Allergic reaction during course 1 was associated with elevated serum levels of IL-1Ra and IFN, while severe hypotension during this course was associated with low IL5 and nitrate. Higher pretreatment CXCL9 level was associated with poorer EFS. Conclusions: This study has confirmed the significant, but manageable treatment-related toxicities of this immunotherapy and identified possible cytokine biomarkers associated with select toxicities and outcome. EFS and OS appear similar to that previously reported on ANBL0032.